Insomnia is associated with worry, cognitive avoidance and low academic engagement in Argentinian university students during the COVID-19 social isolation - Scotta, Ana Verónica (2020)
Fil: Scotta, Ana Verónica. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Escuela de Fonoaudiología; Argentina.